A different drummer : readings in anthropology with a Canadian perspective - Blundell, Valda, 1941-; Chevalier, Jacques M., 1949-; Cox, Bruce Alden (Carleton University Press, 1989)
This volume is a collective production by Carleton University's anthropology caucus, for use in introductory courses in cultural anthropology. It is an alternative to available textbooks which the caucus feels are mainly American in orientation, and not respectful of third and fourth world peoples.